Funkcijsko usmerjeni teoretični okvir za načrtovanje mehatronskih sistemov - Yong, Xu (Strojniški vestnik, 2007)
A new function-oriented theoretical framework for the development of mechatronic system design methods is presented. We include a technology-independent functional description of aspects of a mechatronic system, such as 1) the relations and distinctions among the purpose function, the transformation function and the state transition, 2) the structure of the information processing and 3) the secondary functions. All the discussions arethen summarized in a set of axioms, which then form the basis for devising design models and methods for mechatronic systems.
Keywords: mehatronika; mehatronski sistemi; razvoj; načrtovanje